2003
DOI: 10.1016/s0006-3495(03)70114-3
|View full text |Cite
|
Sign up to set email alerts
|

778.1-Pos Board # B363.1 – Effects of Ca2+ and Temperature on the Force-generating Transition in Cardiac Muscle Studied by Photolysis of Caged-phosphate

Abstract: The genomes of a wide variety of organisms have now been sequenced; a major challenge ahead is to understand the function, regulation and modification of the many encoded gene products. We have been carrying out proteomics approaches to the identification and analysis of signalling pathways in yeast. 121 of 122 protein kinases were cloned and purifed from yeast as GST fusions and analyzed for their ability to phosphorylate 60 different yeast substrates. More than 93% of the kinases exhibited activities that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Exponentials were fit to the simulated transients, and the resultant values for k Pi are listed in Table 2. Over the range of [Ca 21 ] simulated, k Pi at 2 or 4 mM final [Pi] was insensitive to calcium similar to previous studies of skeletal Homsher, 1990, 1992) and cardiac muscle (Martin et al, 2003) but slightly different from cardiac studies that reported a twofold increase in k Pi over this range of [Ca 21 ] (Araujo and Walker, 1996).…”
Section: Model Detailssupporting
confidence: 84%
See 1 more Smart Citation
“…Exponentials were fit to the simulated transients, and the resultant values for k Pi are listed in Table 2. Over the range of [Ca 21 ] simulated, k Pi at 2 or 4 mM final [Pi] was insensitive to calcium similar to previous studies of skeletal Homsher, 1990, 1992) and cardiac muscle (Martin et al, 2003) but slightly different from cardiac studies that reported a twofold increase in k Pi over this range of [Ca 21 ] (Araujo and Walker, 1996).…”
Section: Model Detailssupporting
confidence: 84%
“…This is followed by P i release, which stabilizes a second strongly bound force bearing state, AM.ADP. Studies of both skeletal (Millar and Homsher, 1990;Walker et al, 1992) and cardiac muscle (Araujo and Walker, 1996;Martin et al, 2003) have reported k Pi to be either slightly or not affected by [Ca 21 ], and when compared to k tr in the same preparation, two times faster (Millar and Homsher, 1990;Regnier et al, 1995;Tesi et al, 2000). These results indicate that the tension-generating step is not directly Ca-regulated but suggest a step before force generation is able to sense the steady [Ca 21 ] via the activation level of the thin filament.…”
Section: Introductionmentioning
confidence: 99%